A randomised controlled trial evaluating the utility of a patient Decision Aid to improve clinical trial (RAVES 08.03) related decision-making. Issue 1 (October 2017) - Sundaresan, Puma; Ager, Brittany; Turner, Sandra; Costa, Dan; Kneebone, Andrew; Pearse, Maria; Woo, Henry; Tesson, Stephanie; Juraskova, Ilona; Butow, Phyllis
Abstract: Background and purpose: Randomised controlled trials (RCTs) are considered the 'gold-standard' for evaluating medical treatments. However, patients and clinicians report difficulties with informed consent and recruitment. We evaluated the utility of a Decision Aid (DA) in reducing RCT-related decisional conflict, and improving RCT knowledge and recruitment. Materials and methods: Potential participants for a radiotherapy RCT were invited to participate in the current study. Participants were randomised to receive the RCT's participant information sheet with or without a DA. Questionnaires were administered at baseline, one and six months. The primary outcome measure was decisional conflict. Secondary outcome measures included knowledge regarding and recruitment to the RCT. Results: 129 men were randomised to the DA (63) and control (66) arms. Decisional conflict was significantly lower over 6-months ( p  = 0.048) in the DA arm. Knowledge regarding the RCT was significantly higher at 6 months ( p  = 0.033) in the DA arm. 20.6% of the DA arm (13 of 63) and 9% of the control arm (6 of 66) entered the RCT. Conclusions: This study demonstrates the utility of a DA in reducing decisional conflict and improving trial knowledge in men with cancer who are making decisions regarding RCT participation.